Okun in the Euro: New Evidence from Structural Okun Law's Estimates for the Euro Area, 1979-2019 - Nauro F. Campos; Corrado Macchiarelli; Fotios Mitropoulos (CESifo GmbH, 2024)
This paper provides new estimates of Okun's unemployment-output relationship in euro area countries between 1979 and 2019. We find our structural estimates are stable but substantially lower than the reduced-form estimates that tend to characterise the literature and that the responsiveness of output to unemployment is driven by idiosyncratic factors in both euro core and periphery countries. The results are robust to conditioning on wage bargaining institutional set-ups and, yet, in the euro periphery, we find product market regulation as playing a major role in explaining the significance of Okun's law estimates across countries.
Keywords: E24; E32; J64; G01; 330; economic growth; unemployment; Okun's Law; panel VAR